Peranan Unit Pengelola Kegiatan PNPM Mandiri dalam Meningkatkan Kesejahteraan Masyarakat - Marlina Sinaga; Usman Tarigan; Rosmala Dewi (PERSPEKTIF, 2018)
In the community there are still many publik complaints in terms of the role of govrmment, which is still not well targeted by carrying out duties and responsibilities to the community should every govermment have the ability to further improve the quality of service. As determined by the governement agenciens in the districk pangururan Samosir districk is expected to improve the quality of the government’s more responsible performance as by the government in serving the community. In this case formulation of the formulation of the problem is how the role unit manager activities (upk) pnpm indendent in improving the welfare of society therough savings and loan lending as for the purpose of this study is to find out how UPK PNPM independent office in pangururan district samosir districk. The method in this research is qualitative by using technique of observation, interview and documentation based on the result is this study followed by analyzing the data obtained, then the result is the role of independent upk pnpm in improving the welfare of the community in the districk pangururan samosir districk can be said either. Seen from the progressof members of the spp group as well as, the role of independent UPK PNPM corres panding to the soup. Role